Dior : A new look, a new enterprise (1947-57) - Palmer, Alexandra (South Kensington : V&A Publishing, 2009)
The early years -- A new house, a new femininity -- Couture piracy, protection and litigation -- The Christian Dior Boutique -- Global expansion and licenses -- The celebrity couturier, diplomat and arbiter of taste.
boek
Keywords: Dior